Consideraciones para un Programa de Desarrollo Profesional que orienta al profesor a re-conceptualizar su enseñanza - Ravanal-Moreno, Eduardo (Revista Científica, 2017)
The demands for quality education undoubtedly emphasize the role of the teacher, therefore, there must be a contribution to its development from programs that focus on professional requirements and needs as required for quality education. In this context, a system of professional development that emphasizes the updating and improvement of teacher on discipline and teaching techniques as suggested by public policy in Chile, perhaps, is not a plausible solution to promote quality education, due to the technical rationality that guides it. The article seeks to contribute to the discussion on the pedagogical content knowledge as a hub for professional development biology teacher for its high incidence in teaching. Attention is paid to the aspects involved in professional development and professional teaching knowledge as a necessary requirement for teaching. Some considerations for the design of a professional development model to guide teachers to change their personal epistemology for a new conceptualization of pedagogical practice, including proposed: 1) work with teachers from their professional concerns at a cognitive level, contextual and situated, 2) to promote reflection activity that encourages transit between staff, sources, practical and result of teaching domains, 3) to discuss theoretically the new questions to face the difficulties of teaching and re-structure the pedagogical content knowledge of teacher.